Expression of CCND1, P16 and CDK6 in Human Basal Cell Carcinoma - Eshkoor, Sima Ataollahi (2007)
Basal cell carcinoma (BCC) is the most common cancer among skin cancers. The incidence of cutaneous malignant melanoma (CMM) and non-melanoma skin cancer (NMSC) has increased more than 600% worldwide since the 1940s. Carcinogenesis is a multi-step process involving multiple genetic alterations. The connection between cell cycle proliferation and cancer resulting in deregulated cellular proliferation leads to cancer. Cancer has been associated with disturbances in cell cycle regulation. Recent studies have shown that p16, CDK6 and CCND1 mRNA genes and protein expression are involved in the tumorgenesis of skin cancer. These genes play a role in cell cycle proliferation. In this study, we assessed the expression of a cyclin, a cyclin dependent kinase, and a cyclin kinase inhibitor in skin BCC tissue. Reverse Transcription in situ polymerase chain reaction (RT in situ PCR) and immunohistochemistry (IHC) were used to detect the expression of p16, CDK6 and CCND1 mRNA genes through them of protein expression in human skin BCC tissue The results show that p16, CDK6 and CCND1 mRNA genes and protein are expressed in both normal and human skin BCC tissues. CCND1, CDK6 and p16 mRNA can be found to be expressed mostly in cytoplasm. The mRNA expression in BCC is higher than normal skin tissue. Protein expression of CCND1 and p16 in different BCC tissue are greater than normal skin tissue. p16 mRNA and protein expression is stronger than other genes. RT in situ PCR and IHC analysis data showed significant expression of CCND1, p16 mRNA and protein in BCC compared to normal skin tissue (p<0.05%). Investigation on Iranian samples showed the protein expression of CDK6 is not significant (p>0.05%) but the expression of mRNA for CDK6 gene is significant (p<0.05%). The findings of IHC study on tissue microarray (TMA) demonstrated significant protein expression of p16 and CCND1 genes (p<0.05%) which support findings on Iranian samples. Taken together, these data provide evidence that cell cycle deregulation in G1-phase is a critical event during the course of carcinogenesis of BCC. In conclusion, this study showed that p16, CDK6 and CCND1 are involved in the process of tumorgenesis in human BCC. p16, CDK6 and CCND1 mRNA genes are expressed to induce cell cycle proliferation and also the protein expression of these genes can influence proliferation of the cell cycle. RT in situ PCR study on ten Iranian samples illustrated significant expression of p16 (p=0.026), CDK6 (p=0.015) and CCND1 (p=0.021) mRNA genes (p<0.05%). There is a direct correlation between p16 and CCND1 and also between p16 and CDK6. There is no correlation between CCND1 and CDK6. IHC analysis on the Iranian samples demonstrated significant protein expression of p16 (p=0.019) and CCND1 (p=0.021) (p<0.05%) but CDK6 protein expression is not significant (p=0.082). Direct correlation between p16 and CCND1 was obtained. TMA samples were used for the IHC study only for p16 (p=0.008) and CCND1 (p=0.024) due to insufficient tissue to perform complete study with IHC. Even CDK6 could not be done because of insufficient samples then the result of TMA samples using IHC supports the findings on the Iranian samples about protein expression of CCND1 and p16 genes. RT in situ PCR is a sensitive method to study specific mRNA genes. However there are problems in getting good results as well as their interpretation. IHC on the other hand shows more reliable results. These methods may be used in the clinical setting and as it can be used to predict tumor behavior including cellular proliferation which can affect the mode of therapy.